Development, optimization and implementation of a centralized metabolic soft spot assay. (April 2017) - Paiva, Anthony A; Klakouski, Cheryl; Li, Shu; Johnson, Benjamin M; Shu, Yue-Zhong; Josephs, Jonathan; Zvyaga, Tatyana; Zamora, Ismael; Shou, Wilson Z
Aim: High clearance is a commonly encountered issue in drug discovery. Here we present a centralized metabolic soft spot identification assay with adequate capacity and turnaround time to support the metabolic optimization needs of an entire discovery organization.Methodology: An integrated quan/qual approach utilizing both an orthogonal sample-pooling methodology and software-assisted structure elucidation was developed to enable the assay. Major metabolic soft spots in liver microsomes (rodent and human) were generated in a batch mode, along with kinetics of parent disappearance and metabolite formation, typically within 1 week of incubation.Results & conclusion: A centralized metabolic soft spot identification assay has been developed and has successfully impacted discovery project teams in mitigating instability and establishing potential structure–metabolism relationships.